Paham Keagamaan H. Abdul Jalil bin H. Demang: Analisis Kitab Minhaj al-Umniyah fi Bayani âAqidah Ahl al- Sunnah wa al-JamÃ¢âah - Abbas, Pirhat (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2010)
This article discusses a classic book titled Minhaj al-Umniyah fi Bayani âAqidah Ahl al-Sunnah wa al-JamÃ¢âah by H. AbdulJalil bin H. Demang. This book was produced in 1346 H/1924 M.Philology is used as the method analysis. This article argues thatsomeoneâs belief can be identified by the book she/he wrote. Theanalysis reveals that Minhaj al-Umniyah fi Bayani âAqidah Ahl al-Sunnah wa al-JamÃ¢âah discusses three main issues are: tauhid, fiqh(Islamic law), dan tasawuf (sufism). From the tauhid side, AbdulJalil follows ahl al-sunnah wa al-jamaâah ideology that wasdeveloped by Abu Hasan Asyâari, meanwhile, from the way hedescribes, it tends to follow Muhammad Yusuf al-Sanusi orSanusiyah ideology. From the fiqh side, most of Abdul Jalil articlesdeal with daily prays such as Shalat and less about Muslim fasting,zakat (donation), and hajj. While from tasawuf side, Abdul Jalilgives more explanation about its study that is closer tophilosophical tasawuf.